Analysis of Teacher Organization Improve the Quality of Physical Education Teacher Performance During the Covid-19 Pandemic, in Semarang City High School (Journal of Physical Education and Sports, 2022)
The purpose of this study was to analyze the program, organization, management, infrastructure, human resources, and financing of the Subject Teacher Conference in improving the quality of physical education teacher performance. This research approach uses a qualitative approach. Data analysis techniques using analysis of Strenght, Weakness, Opportunity dan Threat. The results of the strength aspect research have administration, program and governance carried out according to applicable standards. Opportunities with regular activities with the aim of developing the quality of teachers can improve the quality of learning. Weaknesses in coordination and limited governance in a pandemic situation make organizational performance less good. Threats in a pandemic situation do not implement existing programs. The conclusion of this research is that the aspect of the Strength Opportunity Strategy program must foster excellent work standards and foster a sense of meaning. The strategy for the strength opportunity of this organizational aspect is by maximizing the performance of the management. Weakness opportunity strategy where the organization must play a role in motivating teachers to participate in teacher development programs. Weakness threat strategy implements this strategy by submitting proposals to related parties for infrastructure procurement. management strategy by monitoring and evaluating each activity. Strength Opportunity Strategy by making and submitting proposals to related parties.